A STUDY OF COURSE BOOK ANALYSIS OF “ISLAMIC STUDIES AND CHARACTER BASED ON THE CURRICULUM 2013” FOR GRADE X IN THE PERSPECTIVE OF CHARACTER EDUCATION OF THE NATIONAL EDUCATION STANDARD - Mu'amar, Arfan (Studia Religia, 2018)
Abstract: This study is proposed to explore the feasibility aspect of a course book of Islamic studies and character based on curriculum 2013 in the perspective of Character Education of BSNP. Descriptive-evaluative research method is used in this research. Findings are gained in this study. First, of the feasibility aspect, overall material feasibility is considered appropriate but several parts need improvement. For example: in terms of material accuracy, several sources are invalid. Second, the feasibility aspect of the presentation as a whole is considered sufficient. However, several aspects related to the presentation need serious improvement. In the aspect of the feasibility of material presentation there are various findings need to be addressed, such as the presentation in the learning system aspect, independent learning system is mostly used and lack of collaborative learning implementation. This has an impact on students’ difficulty to work together. Third, of the aspect of language feasibility is good where in terms of writing skills, appropriate, correct, and polite Indonesian language standard is used. The Bahasa is politely used so there is no conflict with the norms in society, especially in character education applied in the Islamic education called Akhlakul Karimah (good attitudes). Keywords: Course Book, Curriculum 2013, Character Education.